Limited of Optimum Method for Separation Xylene Isomers by Gas Chromatography - Abdala, Zainab Mahmood; Wadi, Amel Naji; Hassan, Zainab Shaye; Dahaam, Hadi kareem (Al-Nahrain Journal of Science, 2018)
The research includes the prepration of stationary phase of organic material from 10% Di Iso Nonyl Phthalate (DIP) and 5% Di Nonyl Phthalate (DNP) for separation xylene isomers in petroleum derivatives by gas chromatography technique and for the purpose of designation optimal condition and determine the stationary phase selectivity by polar and polar materials separated and calculate the resolution degree for compared with columns chromatographic classic, Poly Ethylene Glycol (PEG) 20% and capillary column (DP5) that separate on stationary phase column from preprate is the best record for the separation xylene isomers, and high resolution degree for meta and para xylene.